SOSIALISASI PEMBERANTASAN PENYALAHGUNAAN NARKOTIKA DAN REHABILITASI YANG MENGHAPUSKAN TUNTUTAN PIDANA DI DESA CAU BELAYU TABANAN - Hariyanto, D.R.S.; Tanaya, P.E.; Yogantara, P.; Purnawan, K.W. (Buletin Udayana Mengabdi, 2023)
The purpose of this community service is to increase awareness in eradicating narcotics abuse, provide information to the public about criminalization for the community and parents/guardians who do not report narcotics abuse and educate related to state policies in terms of rehabilitation. Socialization is directed at the scope of eradicating narcotics abuse. The method used is the method of socialization / counseling, lectures, discussions, question and answer. The results of this service study show that narcotics crime as an extraordinary crime has damaged the nation's next generation and the negative impact caused is extraordinary. There is a criminal threat for the community and parents/guardians who do not report narcotics abuse and there is free rehabilitation for the community as well as loss of criminal responsibility (cannot be prosecuted) if the community volunteered for rehabilitation. This confirms that narcotics is still a threat so that community participation is needed in its eradication, one of which is by reporting narcotics crimes that occur and rehabilitation in terms of healing is important for addicts. This service is very meaningful as an effort to eradicate narcotics abuse, especially by embracing the community so that they can play an active role. Keywords: Narcotics, Eradication, Rehabilitation, Socialization, Tabanan.